Shared genetic architecture between leukocyte telomere length and Alzheimer’s disease - Zhi Cao; Qilong Tan; Hongxi Yang; Chenjie Xu (Alzheimer’s Research & Therapy)
Abstract Background Epidemiological and clinical studies have reported an association between leukocyte telomere length (LTL) and Alzheimer’s disease (AD). However, genetic association between the two phenotypes remains largely unknown. We aimed to elucidate the potential shared genetic architecture between LTL and AD. Methods Summary statistics from genome-wide association studies were obtained from large-scale biobank in European-ancestry populations for LTL (N = 472,174) and AD (71,880 cases, 383,378 controls). We examined the global and local genetic correlation between LTL and AD using linkage-disequilibrium score regression and ρ-HESS. We applied the bivariate causal mixture model (MiXeR) to calculate the number of shared genetic causal variants, and the conditional/conjunctional false discovery rate (condFDR/conjFDR) framework to identify specific shared loci between LTL and AD. Bidirectional two-sample Mendelian randomization (MR) were used to explore the causal associations between LTL and AD. Results We detected a significant genetic correlation between LTL and AD (rg = -0.168). Partitioning the whole genome into 1703 almost independent regions, we observed a significant local genetic correlation for LTL and AD at 19q13.32. MiXeR estimated a total of 360 variants affecting LTL, of which 16 was estimated to influence AD. The condFDR revealed an essential genetic enrichment in LTL conditional on associations with AD, and vice versa. We next identified 8 shared genomic loci between LTL and AD using conjFDR method, of which 4 are novel loci for both the phenotypes. Moreover, 3 shared loci were identified as eQTLs (rs3098168, rs4780338 and rs2680702). All shared loci mapped a subset of 48 credible genes, including USP8, DEXI and APOE. Gene-set analysis identified 18 putative gene sets enriched with the genes mapped to the shared loci. MR analysis suggested that genetically determined AD was causally associated with LTL. Conclusion Our study identified specific shared loci between LTL and AD, providing new insights for polygenic overlap and molecular mechanisms, and highlighting new opportunities for future experimental validation.